Efektivitas Permainan Scrabble Kimia sebagai Media Pembelajaran untuk Materi Sistem Koloid di SMA - Yoga Saputra; Bayharti Bayharti (Universitas Negeri Padang, 2021)
The study aims to reveal the effectiveness of chemistry scrabble game as a learning media for colloidal systems in senior high school. This research is a continuation of research from development research. This type research is quasi-experimental. The population was all students of XI IPA (even semester) 2019 till 2020 at senior high school (SMA N 1) Batang Kapas. This research used 2 classes, the sampling technique is a purposive sampling technique. This research instrument used were student learning outcome. N-Gain value of the experimental class 0.85 (high category) and control class 0,71 (high category), Based on results t-test obtained tcount = 2,77 and ttable = 1,67 it was the chemical scrabble game effectively improved learning outcomes with a high level.